Spatiotemporal Vegetation Dynamics, Forest Loss, and Recovery: Multidecadal Analysis of the U.S. Triple Crown National Scenic Trail Network - Amber R. Ignatius; Ashley N. Annis; Casey A. Helton; Alec W. Reeb; Dylan F. Ricke (Remote Sensing)
The U.S. National Scenic Trail system, encompassing over 12,000 km of hiking trails along the Appalachian Trail (AT), Continental Divide Trail (CDT), and Pacific Crest Trail (PCT), provides critical vegetation corridors that protect diverse forest, savannah, and grassland ecosystems. These ecosystems represent essential habitats facing increasing environmental pressures. This study offers a landscape-scale analysis of the vegetation dynamics across a 2 km wide conservation corridor (20,556 km2), utilizing multidecadal Landsat and MODIS satellite data via Google Earth Engine API to assess the vegetation health, forest disturbance recovery, and phenological shifts. The results reveal that forest loss, primarily driven by wildfire, impacted 1248 km2 of land (9.5% in the AT, 39% in the CDT, and 51% in the PCT) from 2001 to 2023. Moderate and severe wildfires in the PCT (713 km2 burn area) and CDT (350 km2 burn area) corridors exacerbated the vegetation stress and facilitated the transition from forest to grassland. LandTrendr analysis at 15 sample sites revealed slow, multi-year vegetation recovery in the CDT and PCT corridors based on the temporal segmentation and vegetation spectral indices (NBR, NDVI, NDWI, Tasseled Cap). The post-disturbance NBR values remained significantly reduced, averaging 0.31 at five years post-event compared to 0.6 prior to the disturbance. Variations in the vegetation phenology were documented, with no significant trends in the seasonal advancement or delay. This study establishes a robust baseline for vegetation change across the trail system, highlighting the need for further research to explore localized trends. Given the accelerating impacts of climate change and wildfire frequency, the findings underscore the necessity of adaptive conservation strategies to guide vegetation management and ensure the long-term stability and sustainability of vegetation cover in these vital conservation areas.